2017
DOI: 10.15171/hpp.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of low back pain among school age children in Iran

Abstract: Background: Most available data on the prevalence and characteristics of back pain in schoolchildren is related to industrialised and developed countries. The aim of this study was to investigate the prevalence of low back pain (LBP) and potential risk factors among schoolchildren and adolescents in a developing country, Iran.Methods: A cross-sectional study was conducted among 1611 Iranian schoolchildren aged 11–14 years. A self-complete questionnaire was used to assess LBP prevalence, physical leisure activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 25 publications
(62 reference statements)
2
42
0
Order By: Relevance
“…Among these 84 studies, 21 representing a total sample of 18,296 complied with the criteria to be included in the systematic review (Akbar et al, ; Alghadir et al, ; Alghamdi, Nafee, El‐Sayed, & Alsaadi, ; Angarita‐Fonseca et al, ; Chiang, Jacobs, & Orsmond, ; de Oliveira, Chinaglia, & Lima, ; Dianat et al, ; Dianat, Sorkhi, Pourhossein, Alipour, & Asghari‐Jafarabadi, ; Grimmer & Williams, ; Johnson, Adeniji, Mbada, Obembe, & Akosile, ; Korovessis, Koureas, & Papazisis, ; Martínez‐Crespo et al, ; Minghelli, Oliveira, & Nunes, ; Mohseni‐Bandpei, Bagheri‐Nesami, & Shayesteh‐Azar, ; Mwaka, Munabi, Buwembo, Kukkiriza, & Ochieng, ; Noormohammadpour et al, ; Oka, Ranade, & Kulkarni, ; Trevelyan & Legg, ; Vidal, Borràs, Ponseti, Gili, & Palou, ; Watson et al, ; Young, Haig, & Yamakawa, ), 11 with 9,188 subjects were included in the meta‐analysis (Akbar et al, ; Alghadir et al, ; Angarita‐Fonseca et al, ; de Oliveira et al, ; Dianat et al, , ; Martínez‐Crespo et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Trevelyan & Legg, ; Vidal et al, ), and data from 8,218 subjects from 7 studies were included in the IPD meta‐analysis (Akbar et al, ; de Oliveira et al, ; Martínez‐Crespo et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Trevelyan & Legg, ; Vidal et al, ). Figure shows the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these 84 studies, 21 representing a total sample of 18,296 complied with the criteria to be included in the systematic review (Akbar et al, ; Alghadir et al, ; Alghamdi, Nafee, El‐Sayed, & Alsaadi, ; Angarita‐Fonseca et al, ; Chiang, Jacobs, & Orsmond, ; de Oliveira, Chinaglia, & Lima, ; Dianat et al, ; Dianat, Sorkhi, Pourhossein, Alipour, & Asghari‐Jafarabadi, ; Grimmer & Williams, ; Johnson, Adeniji, Mbada, Obembe, & Akosile, ; Korovessis, Koureas, & Papazisis, ; Martínez‐Crespo et al, ; Minghelli, Oliveira, & Nunes, ; Mohseni‐Bandpei, Bagheri‐Nesami, & Shayesteh‐Azar, ; Mwaka, Munabi, Buwembo, Kukkiriza, & Ochieng, ; Noormohammadpour et al, ; Oka, Ranade, & Kulkarni, ; Trevelyan & Legg, ; Vidal, Borràs, Ponseti, Gili, & Palou, ; Watson et al, ; Young, Haig, & Yamakawa, ), 11 with 9,188 subjects were included in the meta‐analysis (Akbar et al, ; Alghadir et al, ; Angarita‐Fonseca et al, ; de Oliveira et al, ; Dianat et al, , ; Martínez‐Crespo et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Trevelyan & Legg, ; Vidal et al, ), and data from 8,218 subjects from 7 studies were included in the IPD meta‐analysis (Akbar et al, ; de Oliveira et al, ; Martínez‐Crespo et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Trevelyan & Legg, ; Vidal et al, ). Figure shows the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 21 studies, 19 used standardized self‐report questionnaires to determine the prevalence of LBP (Akbar et al, ; Alghadir et al, ; Alghamdi et al, ; Angarita‐Fonseca et al, ; Chiang et al, ; de Oliveira et al, ; Dianat et al, , ; Grimmer & Williams, ; Johnson et al, ; Martínez‐Crespo et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Mwaka et al, ; Noormohammadpour et al, ; Oka et al, ; Trevelyan & Legg, ; Vidal et al, ; Watson et al, ). One study used a non‐standardized, ad hoc self‐questionnaire (Young et al, ), and the last one verbally asked the subjects a non‐standardized question (Korovessis et al, ).Twelve of these 21 studies (including the two studies which did not use standardized self‐report questionnaires), also used some form of physical examination (Akbar et al, ; Alghadir et al, ; Chiang et al, ; de Oliveira et al, ; Johnson et al, ; Minghelli et al, ; Mohseni‐Bandpei et al, ; Mwaka et al, ; Noormohammadpour et al, ; Trevelyan & Legg, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean weight of the participants were 49.7 (SD 11.36) kg; [girls ≤13 years: 48.1 (SD 10.5) kg, girls ≥14 years: 47.2 (SD 11.7) kg, boys ≤13 years: 51.1 (SD 10.1) kg and boys ≥14 years: 53.2 (SD 12.2) kg] and BMI, 19.9 (3.83) kg/m 2 [girls ≤13 years: 19.6 (SD 3.8) kg/m 2 , girls ≥14 years: 20.0 (SD 4.2) kg/m 2 , boys ≤13 years: 19.8 (SD 3.3) kg/m 2 and boys ≥14 years: 20.3 (SD 4.0) kg/m 2 ]. More details on characteristics of the physical leisure activity, use of schoolbags and psychological trait among the schoolchildren are presented in [ 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has shown that MSP is very common among school children and youth [ 5 7 ]. According to the literature, the reported incidence of neck, shoulder and spinal pain in school children and adolescents ranges from 7% to 74% [ 5 , 6 , 8 10 ]. There is evidence that MSP in childhood and adolescence is a contributory factor for experiencing such complaints in adulthood [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%